Cationic Proteins of Polymorphonuclear Leukocyte Lysosomes II. Composition, Properties, and Mechanism of Antibacterial Action - Zeya, H. I. (1966)
Zeya, H. I. (University of North Carolina, Chapel Hill), and J. K. Spitznagel. Cationic proteins of polymorphonuclear leukocyte lysosomes. II. Composition, properties, and mechanism of antibacterial action. J. Bacteriol. 91:755–762. 1966.—A basic proteins fraction from guinea pig polymorphonuclear (PMN) granules was obtained by acid extraction and precipitation with 20% (v/v) ethyl alcohol. The fraction accounted for most of the antibacterial activity of the PMN granules and corresponded to the antibacterial cationic components of intact granules (bands I, II, and III) resolved by zone electrophoresis. Absence from the fraction of components identical to the enzymatic components of intact lysosomes showed that the fraction was essentially free from lysosomal enzymes. The amino acid analysis of proteins in the fraction gave a preponderance of basic amino acids (25%), especially of arginine (16%). The comparative amino acid analysis showed that the lysosomal cationic proteins (LCP) fraction was markedly different from nuclear histones. The LCP fraction manifested antibacterial activity against certain gram-positive and gram-positive microorganisms, including Candida albicans, and exhibited stoichiometric relationship in its activity. Microorganisms treated with LCP fraction were agglutinated. Anionic substances such as nucleic acids, heparin, and endotoxin effectively blocked the antibacterial activity of the fraction. The LCP fraction caused suppression of oxygen uptake by bacterial cells and damaged the permeability barriers of cells as manifested by rapid release of P(32) as well as ultraviolet-absorbing material at 260 mμ, in the supernatant fluid.